ANALISIS FAKTOR KENYAMANAN DAN KETERGANTUNGAN MAHASISWA PADA SMARTPHONE YANG MENGAKIBATKAN STRES - Antonius Satria Hadi (Jurnal Bisnis Darmajaya, 2020)
Convenience is a trigger factor for dependency which in turn will trigger stress. Convenience can be said as a pleasant feeling when someone uses a smartphone. This study aims to determine the factor that influence stress caused by smartphone (technology) which is convenience. Previous researchers called the stress caused by technology is technostress. The technostress in this study is caused by dependency, and dependency is influenced by convenience variable. Data obtained from questionnaires distributed with purposive sampling techniques to undergraduate students at UGM in Yogyakarta. Result of this study shows that convenience have positive and significant effect to dependency and dependency itself have positive and significant effect to technostress. All hypotheses on this research are accepted. Each of hypotheses discussed detailly in this article.Keywords — convenience, dependency, technostress, smartphone